Endometrial thickness cut-off value by transvaginal ultrasonography for screening of endometrial pathology in premenopausal and postmenopausal women - Yu Ran Park; Shin Wha Lee; Yeongsin Kim; In Young Bae; Hong-Kyu Kim; Jaewon Choe; Yong-Man Kim (Korean Society of Obstetrics and Gynecology, 2019)
ObjectiveTo assess the clinical usefulness and diagnostic accuracy of ultrasonographic measurement of endometrial thickness (ET) in women with endometrial hyperplasia or cancer (EH+).MethodsThis retrospective cohort study included 29,995 consecutive women who underwent transvaginal ultrasonography (TVS) for an incidental finding of a thickened endometrium at the health screening and promotion center at Asan Medical Center between 2006 and 2010. Among 959 patients with endometrial abnormalities, 92 patients were included in this study. A total of 867 patients were excluded: 416 were lost to follow-up; 263 did not undergo endometrial biopsy; 155 had endometrial polyps; 17 had submucosal myomas; and 16 had insufficient tissue samples. Endometrial histology was the reference standard for calculating accuracy.ResultsOf the 92 patients, 78 (84.8%) had normal pathology, while 14 (15.2%) had endometrial pathology (EH+), including 5 patients (35.7%) with simple hyperplasia without atypia, 3 (21.4%) with complex hyperplasia, and 6 (42.9%) with endometrial carcinoma, all stage Ia. The area under the receiver-operating characteristic curve was 0.75 (95% confidence interval [CI], 0.593-0.906). The cut-off value for ET was 8 mm, indicating that TVS ET had a fair accuracy in diagnosing carcinoma, had a sensitivity of 100% (95% CI, 62.9-100.0%) and a specificity of 24.3% (95% CI, 15.2-36.3%).ConclusionTVS is useful for detecting EH+, with a cut-off value for ET of 8 mm having a high sensitivity for detecting endometrial pathologies and the ability to identify women highly unlikely to have EH+, thereby avoiding more invasive endometrial biopsy.